2019
DOI: 10.1177/1054773819867250
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Dog-Assisted Therapy Program to Enhance Quality of Life in Institutionalized Dementia Patients

Abstract: The aim of this study was to assess the effectiveness of a dog-assisted therapy intervention to enhance quality of life in persons with dementia institutionalized in a public care home and to study its effect on the use of psychotropic medications. A dog-assisted therapy intervention was designed, in which 34 residents of a public care home in Cuenca (Spain) participated. The participants were assigned to two groups, an experimental and a control group. The program consisted of one 50-min session per week duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…In summary, it can be concluded that the best evidence in the affective and behavioral areas can have a positive influence at the psychosocial level and on the quality of life [17][18][19][20][21], which provides more data on the potential of these interventions as a complement to and support for the theories related to motivation, attention, social support, learning, and activation of the experimental system developed to date [23].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In summary, it can be concluded that the best evidence in the affective and behavioral areas can have a positive influence at the psychosocial level and on the quality of life [17][18][19][20][21], which provides more data on the potential of these interventions as a complement to and support for the theories related to motivation, attention, social support, learning, and activation of the experimental system developed to date [23].…”
Section: Discussionmentioning
confidence: 96%
“…Data collection was conducted in the beginning, at four months, and at eight months of intervention by occupational therapists or working psychologists from the participating centers. For the measurement of the four areas of study or dependent variables, the following scales were used (all widely used in the centers and studies consulted) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]: for the cognitive area, the Mini-Cognitive State Examination (MEC-30) with a weighted kappa index of 0.637; a sensitivity of 89.8% and specificity of 75.1% [29]; for the functional area, the modified Barthel index (kappa between 0.47 and 1.00 with respect to the inter-observer and between 0.84 and 0.97 for the intraobserver) [30]; for the effective area, the Cornell Scale of Depression in dementia (CSDD) (kappa between 0.61 and 0.84 and a total reliability of 0.93, internal consistency of 0.81) [31,32], and for the behavioral area, the Neuropsychiatric Disorders Inventory (NPI) with a Pearson's correlation index of 0.879 for the severity scale and 0.92 for the stress scale [33]. In addition, the following independent sociodemographic variables were collected from the clinical records: sex, age, education (basic, middle and higher) and center, and the clinical data collected included: type of disorder additional to dementia (cardiovascular disease, depression, anxiety and diabetes), time of residence, and regular daily therapies (occupational therapy, physical therapy) and weekly complementary therapies (psychological, socio-cultural animation and alternative therapy: music therapy, work therapy and geronto-gymnastics).…”
Section: Instruments and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary study conducted by Menna et al [ 55 ] found that the repeated multisensory stimuli (verbal, visual, tactile) provided by the therapy dog were effective. AAT has been considered a meaningful activity that provides stimulation and social interaction [ 56 , 57 ], and improves the participants’ mood [ 20 , 58 , 59 ]. Furthermore, interventions that favor communication and an optimistic atmosphere can have a positive impact on social interactions [ 9 , 60 , 61 ], as our study reflected.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to ethological characteristics, dogs not only learn through play, just like children, but are prone to establishing active relationships, communications, and interactions [ 22 ]. In recent years, several studies have been conducted on the effectiveness of dog-assisted therapies in AD patients [ 10 , 23 , 24 , 25 , 26 , 27 ], but some studies concluded that the improvements observed were not always significant [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%